Data Mining with Python Theory, Application, and Case Studies - Wu, Di (Chapman and Hall/CRC the Python Series, 2024)
This book focuses on the hands-on approach to learning Data Mining. It showcases how to use Python Packages to fulfill the Data Mining pipeline, which is to collect, integrate, manipulate, clean, process, organize, and analyze data for knowledge